Creation of a Novel Nomogram Based on the Direct Bilirubin-To-Indirect Bilirubin Ratio and Lactate Dehydrogenase Levels in Resectable Colorectal Cancer - Ma, Yifei; Shi, Lulu; Lu, Ping; Yao, Shuang; Xu, Hongli; Hu, Junjie; Liang, Xin; Liang, Xinjun; Wei, Shaozhong (Frontiers in Molecular Biosciences, 2021)
Background: Recently, many studies have suggested that bilirubin is associated with the prognosis of colorectal cancer (CRC). Conversely, there is substantial evidence that lactate dehydrogenase (LDH) levels are associated with the prognosis of cancer. Therefore, we sought to find a novel marker based on the above to predict prognosis in patients with resectable CRC. Methods: A total of 702 patients from Hubei Cancer Hospital were included. The whole population was randomly divided into training (n=491) and testing (n=211) cohorts. Next, we established a new index based on direct bilirubin, indirect bilirubin and LDH levels. Chi-square tests, Kaplan-Meier survival analyses, and Cox regression analyses were used to evaluate prognosis. The prediction accuracies of models for overall survival (OS) and disease-free survival (DFS) were estimated through Harrell’s concordance index (C-index) and the Brier score. Results: The median DFS duration was 32 months (range: 0 months -72.6 months), whereas the median OS duration was 35 months (range: 0 months -73.8 months). In addition, a new indicator, (DIR.LDH) (HR: 1.433; 95% CI, 1.069-1.920) could independently predict outcomes in CRC patients. Moreover, the module based on DIR.LDH was found to have exceptional performance for predicting OS and DFS. The C-index of the nomogram for OS was 0.802 (95% CI, 0.76-0.85) in the training cohort and 0.829 (95% CI, 0.77-0.89) in the testing cohort. The C-index of the nomogram for DFS was 0.774 (95% CI, 0.74-0.81) in the training cohort and 0.775 (95% CI, 0.71-0.84) in the testing cohort. Conclusion: We successfully established a novel module to guide clinical decision-making for CRC.